Legal Position Of A Deed Made By A Substitute Notary Who Does Not Meet The Requirements For Appointment - Puspitasari, Dewi (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2024)
This research was conducted to analyze the validity of deeds made by or before a Substitute Notary who did not meet the requirements for his/her appointment and to find out what authority and responsibility the Substitute Notary must accept. In this case, what has been done is not in accordance with Article 33 paragraph (1) UUJN, as explained that the requirements to become a Substitute Notary and temporary Notary are Indonesian citizens who have a law degree and have worked as an employee of a Notary’s office for at least 2 (two) consecutive years. In reality, when a Substitute Notary in his/her appointment does not comply with the applicable regulations, then the deed made by the Notary becomes a problem regarding the validity of the deed made. This research uses the Normative Juridical method (legal research) with a statutory approach and a conceptual approach. The results of this scientific research are that firstly, the deed made by the Substitute Notary is valid, but the deed is degraded to a private deed, because the Substitute Notary does not have the authority as stated in Article 15 and the Substitute Notary does not meet the requirements for appointment in Article 33 paragraph (1) of the Notary Law, and does not meet the requirements stipulated in Article 1868 of the Civil Code, so that according to Article 1869 of the Civil Code the deed becomes a private deed. Secondly, the Substitute Notary cannot be fully blamed, because the Substitute Notary is the appointed Substitute Notary. The Substitute Notary is not authorized to make deeds, and the Substitute Notary is independently responsible for the deeds he/she makes, where the Substitute Notary can be sued in civil court for damages, if the parties demand damages.